2015
DOI: 10.1007/s00417-015-3192-y
|View full text |Cite
|
Sign up to set email alerts
|

Micro-invasive 360-degree suture trabeculotomy after successful canaloplasty – one year results

Abstract: Micro-invasive 360-degree suture trabeculotomy represents a simple and safe minimal invasive ab interno technique to postoperatively enhance the IOP-lowering and drug-sparing effect of canaloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In most cases, a minimal invasive 360‐degree suture trabeculotomy was performed, as described in an earlier study (Seuthe et al. ). In those cases where the IOP afterwards still was not acceptable, a deep sclerectomy had to be performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, a minimal invasive 360‐degree suture trabeculotomy was performed, as described in an earlier study (Seuthe et al. ). In those cases where the IOP afterwards still was not acceptable, a deep sclerectomy had to be performed.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where canaloplasty did not achieve a sufficient and sustained IOP, a 360‐degree suture trabeculotomy can be performed as an effective and micro‐invasive way to gain an additional IOP‐reducing effect after canaloplasty by removing the canaloplasty suture via the anterior chamber (Seuthe et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main variation of this novel technique is the creation of a second deep scleral flap facilitating orientation and probing of Schlemm's canal and creating an additional aqueous outflow and drainage into the suprachoroidal space . We could also show that an additional IOP reduction of 41.2% can be achieved by microinvasive 360°trabeculotomy under topical anaesthesia in cases where target IOP was not achieved (Seuthe et al 2015).…”
mentioning
confidence: 78%
“…The authors also reported that in the case of insufficient IOP levels being reached, a 360°suture trabeculotomy during the follow-up phase can be carried out. 81 No serious or sight-threatening complications occurred. Authors emphasized that in cases where probing with the suture fails, there still remains the option to use a conventional microcatheter or switch to sclerectomy with collagen sheet implantation in the suprachoroidal space.…”
Section: Cathetherless Canaloplastymentioning
confidence: 93%